Association of specific haplotypes of D2 dopamine receptor gene with vulnerability to heroin dependence in 2 distinct populations - Xu, Ke; Lichtermann, Dirk; Lipsky, Robert H; Franke, Petra; Liu, Xiehe; Hu, Ying; Cao, Liping; Schwab, Sibylle G; Wildenauer, Dieter B; Bau, Claiton H D; Ferro, Erica; Astor, Will; et al. (Archives of general psychiatry, 2004)
Dopamine receptor-mediated pathways play critical roles in the mechanism of addiction. However, associations of the D(2) dopamine receptor gene (DRD2) with substance abuse are controversial. To determine whether susceptibility sites resided at DRD2. Haplotype-based case-control analysis of 2 distinct populations using 10 single nucleotide polymorphisms (SNPs) with heroin dependence. Universities of Mainz and Bonn, Germany, and 3 local hospitals in southwestern China. Patients Cases and control subjects recruited from China (486 cases, 313 controls) and Germany (471 cases, 192 controls). Genotyping for 10 SNPs by 5'-exonuclease fluorescence assays. The D' value of linkage disequilibrium and haplotypes were generated by the expectation-maximization algorithm. Genotype, allele, and haplotype frequencies were compared between cases and controls by chi(2) tests constructed for each population. An additional 32 SNPs randomly distributed in the genome were genotyped for detecting population admixture in the 2 populations. A haplotype block of 25.8 kilobases (kb) was defined by 8 SNPs extending from SNP3 (TaqIB) at the 5' end to SNP10 site (TaqIA) located 10 kb distal to the 3' end of the gene. Within this block, specific haplotype cluster A (carrying TaqIB1 allele) was associated with a high risk of heroin dependence in Chinese patients (P = 1.425 x 10(-22); odds ratio, 52.80; 95% confidence interval, 7.290-382.5 for 8-SNP analysis). A putative recombination "hot spot" was found near SNP6 (intron 6 ins/del G), creating 2 new daughter haplotypes that were associated with a lower risk of heroin dependence in Germans (P = 1.94 x 10(-11) for 8-SNP analysis). There was no evidence of population stratification in either population. These results strongly support a role of DRD2 as a susceptibility gene with heroin dependence in Chinese patients and was associated with low risk of heroin dependence in Germans.